2015
DOI: 10.3233/ves-150554
|View full text |Cite
|
Sign up to set email alerts
|

Ocular vestibular evoked myogenic potentials in response to air-conducted 500 Hz short tones: Effect of stimulation procedure (monaural or binaural), age and gender

Abstract: The oVEMP obtained after binaural and monaural stimulation are very similar, and they are largely independent from age and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…As a result, these responses would have been unidentified, resulting in lower oVEMP response rates in the elderly (4). This study appears to be consistent with earlier findings (4,15,18,22,(31)(32)(33)(34)(35)(36). However, those studies showed different onset age of reductions in oVEMP response rates and amplitudes.…”
Section: E Ects Of Aging On Ovemps Responsesupporting
confidence: 91%
“…As a result, these responses would have been unidentified, resulting in lower oVEMP response rates in the elderly (4). This study appears to be consistent with earlier findings (4,15,18,22,(31)(32)(33)(34)(35)(36). However, those studies showed different onset age of reductions in oVEMP response rates and amplitudes.…”
Section: E Ects Of Aging On Ovemps Responsesupporting
confidence: 91%
“…However, a more recent study of Versino et al (2015) did not reveal a gender effect on the oVEMP responses. Another drawback of the present study was our inability to make a valid comparison between the normal group and the patient group.…”
Section: Shortcomings and Future Researchmentioning
confidence: 74%
“…Con respecto al sexo de los sujetos estudiados, se observa una mayor proporción del femenino (76%), hecho que no afecta ni sesga el estudio al fundamentarse en los hallazgos reportados por Versino et al 12 , quienes compararon las respuestas obtenidas en los oVEMP según el sexo y no hallaron diferencia significativa en cuanto a los parámetros y las modalidades de estimulación.…”
Section: Discussionunclassified
“…Con respecto al comportamiento de la amplitud, un estudio realizado en 2013 reporta hallazgos obtenidos en pacientes con neuritis vestibular a los que se registraron los oVEMP en respuesta a un estímulo acústico en la frecuencia de 1000 Hz mediante tono burst. Se halló que estos pacientes presentaban una alta proporción de anomalías en la estimulación por vía aérea 12 , lo que sugiere que la frecuencia de 1000 Hz es útil para medir la actividad del nervio vestibular superior, y respalda en cierta forma que esta frecuencia sea utilizada como indicador de respuesta utricular.…”
Section: Discussionunclassified